A method for preparing an aluminum-silicon alloy reinforced with in-situ generated silicon carbide

By reacting in situ on a silicon dioxide substrate to generate silicon carbide particles, the problems of high raw material costs, complex process and high equipment requirements in the existing silicon carbide particle-enhanced aluminum-based alloy preparation methods are solved, and the performance of aluminum-silicon alloys is improved and simplification of the process.

CN116426787BActive Publication Date: 2025-02-25CHANGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310466192.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2025-02-25
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

The existing preparation methods for silicon carbide particle reinforced aluminum-based alloys have problems such as high raw material costs, complex processes and high equipment requirements.

Method used

Silicon carbide is generated by in situ reaction on a silica substrate, and silicon carbide particles are generated by chemical reaction between carbon nanomaterials and aluminum and silica, thereby enhancing the performance of aluminum-silicon alloys.

Benefits of technology

This method improves the toughness, elongation and thermal conductivity of aluminum-silicon alloys, and has a simple process and adjustable shape performance, making it suitable for industrial scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004202342800000011
    Figure HDA0004202342800000011
  • Figure HDA0004202342800000012
    Figure HDA0004202342800000012
Patent Text Reader

Abstract

The present invention belongs to the technical field of aluminum silicon alloys, and specifically discloses a method for preparing an aluminum silicon alloy reinforced with silicon carbide generated in situ. A carbon nano-slurry is coated on the inner wall surface of a clean silicon dioxide substrate, and a pure aluminum ingot is melted and poured into the silicon dioxide substrate coated with the carbon nano-slurry under the condition of passing an inert gas, and then the ingot is left to stand at the melting temperature for heat preservation. After the heat preservation is completed, the aluminum silicon alloy reinforced with silicon carbide is obtained. The silicon carbide generated in situ by the method improves the toughness, elongation and thermal conductivity of the aluminum silicon alloy as a reinforcing phase, and at the same time, the silicon carbide content in the prepared aluminum silicon alloy can be controlled. The method has a simple preparation process, low requirements for smelting equipment, is easy to industrialize, and has a high application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum-silicon alloys, and in particular relates to a method for preparing an aluminum-silicon alloy reinforced with in-situ generated silicon carbide. Background Art

[0002] Silicon carbide is a common ceramic phase with high melting point, strong rigidity, high hardness, good thermal stability, strong room temperature corrosion resistance and low thermal expansion coefficient. Silicon carbide reinforced aluminum-based composite materials have the characteristics of light weight, high specific modulus and excellent wear resistance, and are widely used in the fields of aerospace, automobiles and electronic products. Today, the preparation methods of silicon carbide particle reinforced aluminum-based alloys mainly include liquid stirring method, rheological casting technology, melt infiltration method and in-situ synthesis method.

[0003] The in-situ synthesis method refers to a technology that directly synthesizes reinforcements in the matrix through chemical reactions. Compared with other preparation methods, the in-situ synthesis method has the following advantages: (1) The in-situ synthesized reinforcements are thermodynamically stable in the matrix and have little thermal decomposition under high temperature conditions; (2) The interface between the reinforcement and the matrix is ​​clean and has strong interfacial bonding; (3) The in-situ synthesized particles are small in size and evenly distributed in the matrix.

[0004] Chinese patent CN106893880A discloses a method for preparing an in-situ hot-pressed silicon carbide particle-reinforced aluminum-based composite material, wherein aluminum powder, silicon powder, and carbon powder are mixed in a certain molar ratio, ground by mechanical alloying, and sintered under pressure and high temperature. This method has high raw material costs, and the preparation process requires pressure treatment, and the process is complicated.

[0005] Chinese patent CN109182813A discloses a method for preparing a carbon nanotube-reinforced aluminum-based composite material by growing carbon nanotubes on the surface of silicon micropowder using an in-situ chemical vapor deposition process. The growth rate of the carbon nanotubes in this method is low; the preparation process is complex and requires a high temperature and high pressure environment, using mixed gases such as hydrogen and methane, and has high requirements for equipment and the environment. Summary of the invention

[0006] The purpose of the present invention is to provide an aluminum-silicon alloy reinforced with in-situ generated silicon carbide, in which silicon carbide is generated by an in-situ reaction between silicon dioxide, aluminum and carbon nanomaterials, thereby improving the toughness, elongation, thermal conductivity and other properties of the aluminum-silicon alloy. At the same time, this method also has the advantages of simple preparation process and adjustable shape performance.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing an aluminum-silicon alloy reinforced with in-situ generated silicon carbide comprises the following steps:

[0009] (1) preparing an additive slurry: uniformly dispersing the carbon nanomaterial in a solvent, adding a thickener and a binder, and uniformly stirring to obtain an additive slurry;

[0010] (2) uniformly coating the added slurry of step (1) on the inner surface of the silica substrate, drying and cooling, to obtain a silica substrate with a carbon nanomaterial coated on the inner surface;

[0011] (3) Under the protection of an inert gas, a molten aluminum solution is poured into the silicon dioxide substrate whose inner surface is coated with a carbon nanomaterial in step (2), and the mixture is kept at 700-800° C. for 3 h, and then cooled; the silicon dioxide substrate is removed, and surface residues are cleaned to obtain an aluminum silicon alloy reinforced with a carbon nanomaterial.

[0012] Furthermore, the carbon content of the carbon nanomaterial is greater than 98%, and the grayscale is less than 1%; the silicon dioxide content of the silicon dioxide substrate is greater than or equal to 99.9%; and the aluminum content in the molten aluminum solution is greater than or equal to 99.9%.

[0013] The carbon nanomaterial used in the present invention is any one of carbon nanotubes, graphene and graphene oxide; the solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide, dioxane, ethanol, ethylene glycol, butanone and toluene.

[0014] Furthermore, the mass fraction of the carbon nanomaterial in the added slurry of step (1) is 10-60wt.%; further, the mass fraction of the carbon nanomaterial in the added slurry of step (1) is 20-50wt.%.

[0015] Furthermore, in step (1), the sum of the mass of the thickener and the adhesive is 1-2wt.% of the mass of the added slurry; preferably 1wt.%; preferably, the thickener is polyvinylidene fluoride, the adhesive is an acrylic resin curable hot melt adhesive, and the ratio of the thickener to the adhesive is 3:2.

[0016] Furthermore, in step (2), the coating thickness of the added slurry is 0.5-1.5 mm, preferably 1 mm.

[0017] Furthermore, in step (2), the drying temperature is 70-90°C and the time is 20-50 min; preferably, the drying temperature is 80°C and the time is 30 min.

[0018] Furthermore, in step (3), the static insulation temperature is 700° C. and the insulation time is 3 hours.

[0019] Furthermore, in step (3), the inert gas is argon.

[0020] Furthermore, in step (3), the pouring amount of the molten aluminum solution is 0.99-1.05 times the mass of the prepared workpiece.

[0021] Beneficial technical effects of the present invention:

[0022] (1) In terms of microstructure, silicon carbide particles are generated through the in-situ reactions of SiO2+Al=Al2O3+Si and Si+C=SiC, thereby effectively strengthening the aluminum-silicon alloy.

[0023] (2) Aluminum-silicon alloys with different properties can be prepared by changing the concentration of carbon nano-slurry, so as to adapt to different industrial uses. The aluminum-silicon alloy prepared by the present invention is widely used due to its advantages such as high hardness, good thermal stability and corrosion resistance, and low thermal expansion coefficient.

[0024] (3) The present invention adopts a molded silica model, which can quickly manufacture products of various specifications, and therefore has good application prospects for workpieces that can be molded in one step; the production process is simple, controllable, and applicable, and can be produced on an industrial scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The microstructure morphology of the aluminum-silicon alloy prepared in Examples 1 to 4;

[0026] Figure 2 This is the XRD pattern of the aluminum-silicon alloy prepared in Example 3. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings. Comparative examples and examples of carbon nanomaterial reinforced aluminum silicon alloys prepared by conventional methods are given below.

[0028] The carbon nanomaterial used in the following embodiments is carbon nanotubes with a molecular weight of 12.01, a hexagonal crystal system, a tube diameter of 10-20nm, a tube length of 2-8 microns, a purity greater than 98%, and a grayscale less than 1%; a slight change in tube length and diameter will not cause much change in performance. When the purity decreases, the carbon content will also decrease, thereby affecting the performance.

[0029] The thickener is polyvinylidene fluoride, and the binder is an acrylic resin curable hot melt adhesive. The usage ratio of the thickener and the binder is 3:2. The mass of the two is 1wt.%, and the content is relatively small. During the material preparation process, it will decompose as the temperature rises, and ultimately the content in the material is extremely small.

[0030] Specific methods for testing yield strength, tensile strength and elongation: The testing machine used in the test is TSE504D universal testing machine. The samples used in the test are all prepared by wire cutting and lathe, and meet the standard of "GB / T228-2010 Metal Material Tensile Test Part 1: Room Temperature Test Method". According to different orientations, the specimens are divided into radial (RD), axial (AD), and 45° specimens. The test is carried out at room temperature. During the test, an extensometer is added to collect strain data. The displacement control mode is adopted, and the nominal loading rate is 0.5mm*min. -1 .Through the experiment, three properties were obtained: YS (yield strength), UTS (tensile strength), and EL (elongation). In order to ensure the reliability of the data, at least 6 samples were taken for RD samples, and at least 3 samples were taken for AD and 45° samples.

[0031] Thermal conductivity test method: Laser emission method - Laser thermal conductivity directly tests the thermal diffusion coefficient of the material. The basic principle is that at a certain temperature controlled by the furnace, the laser source emits light pulses that evenly irradiate the lower surface of the sample to heat the sample evenly. The corresponding temperature rise process on the upper surface of the sample is measured by an infrared detector to obtain the relationship curve between the temperature (detector signal) increase and time. The thermal diffusion coefficient is obtained by fitting with a suitable model. The specific heat capacity data can be obtained by comparing with the standard sample, and finally the thermal conductivity data can be calculated by the formula (thermal conductivity = thermal diffusion coefficient × specific heat capacity × density).

[0032] Example 1

[0033] (1) Preparation of additive slurry: Disperse carbon nanotube powder in a solvent to prepare a carbon nanomaterial suspension, ultrasonically disperse the suspension for 30 minutes, and then add appropriate amounts of thickener and adhesive. After uniform stirring, an additive slurry is obtained. The carbon nanotube content of the obtained slurry is 10wt.%, the content of the thickener and adhesive is 1wt.%, and the rest is solvent;

[0034] (2) Take a certain amount of the slurry prepared in step (1) and evenly apply it on the inner surface of a silica quartz container (volume: 200 ml) with an inner surface area of ​​100 cm 2 The slurry thickness is 1 mm, and then it is placed in a vacuum drying oven, dried at 80 ° C for 30 minutes, and then placed in the air to cool for use. The carbon content is 1g;

[0035] (3) Under the condition of passing inert gas (such as argon, etc.), pour 700°C molten aluminum liquid into the silica quartz container with the inner surface coated with carbon nanomaterial slurry in step (2) (about 500g), then stand at the molten temperature of 700°C for 3 hours, then take it out and place it in the air to cool to room temperature. Then break the silica quartz container and take out the cast aluminum silicon alloy;

[0036] (4) removing the silicon dioxide residue on the surface of the material in step (3) by grinding, thereby obtaining an aluminum silicon alloy reinforced with carbon nanomaterials having a shape consistent with the shape of the vessel.

[0037] The aluminum-silicon alloy obtained in this embodiment has an average yield strength of about 385 MPa, an average tensile strength of about 407.5 MPa, an average elongation of about 12.1%, and an average thermal conductivity of 225.2 w / mk.

[0038] Example 2

[0039] (1) Preparation of additive slurry: Disperse carbon nanotube powder in a solvent to prepare a carbon nanomaterial suspension, ultrasonically disperse the suspension for 30 minutes, and then add appropriate amounts of thickener and adhesive. After uniform stirring, an additive slurry is obtained. The carbon nanotube content of the obtained slurry is 20wt.%, the content of thickener and adhesive is 1wt.%, and the rest is solvent;

[0040] (2) Take a certain amount of the slurry prepared in step (1) and evenly apply it on the inner surface of a silica quartz container (volume: 200 ml) with an inner surface area of ​​100 cm 2 The slurry thickness is 1 mm, and then it is placed in a vacuum drying oven, dried at 80 ° C for 30 minutes, and then placed in the air to cool for use. The carbon content is 2g;

[0041] (3) Under the condition of passing inert gas (such as argon, etc.), pour 700°C molten aluminum liquid into the silica quartz container with the inner surface coated with carbon nanomaterial slurry in step (2) (about 500g), then stand at the molten temperature of 700°C for 3 hours, then take it out and place it in the air to cool to room temperature. Then break the silica quartz container and take out the cast aluminum silicon alloy;

[0042] (4) removing the silicon dioxide residue on the surface of the material in step (3) by grinding, thereby obtaining an aluminum silicon alloy reinforced with carbon nanomaterials having a shape consistent with the shape of the vessel.

[0043] The aluminum-silicon alloy obtained in this embodiment has an average yield strength of about 425 MPa, an average tensile strength of about 468 MPa, an average elongation of about 10.9%, and an average thermal conductivity of 179.7 w / mk.

[0044] Example 3

[0045] (1) Preparation of additive slurry: Disperse carbon nanotube powder in a solvent to prepare a carbon nanomaterial suspension, ultrasonically disperse the suspension for 30 minutes, and then add appropriate amounts of thickener and adhesive. After uniform stirring, an additive slurry is obtained. The carbon nanotube content of the obtained slurry is 30wt.%, the content of the thickener and adhesive is 1wt.%, and the rest is solvent;

[0046] (2) Take a certain amount of the slurry prepared in step (1) and evenly apply it on the inner surface of a silica quartz container (volume: 200 ml) with an inner surface area of ​​100 cm 2 The slurry thickness is 1 mm, and then it is placed in a vacuum drying oven, dried at 80°C for 30 min, and then placed in the air to cool for use. The carbon content is 3 g;

[0047] (3) Under the condition of passing inert gas (such as argon, etc.), pour 700°C molten aluminum liquid into the silica quartz container with the inner surface coated with carbon nanomaterial slurry in step (2) (about 500g), then stand at the molten temperature of 700°C for 3 hours, then take it out and place it in the air to cool to room temperature. Then break the silica quartz container and take out the cast aluminum silicon alloy;

[0048] (4) removing the silicon dioxide residue on the surface of the material in step (3) by grinding, thereby obtaining an aluminum silicon alloy reinforced with carbon nanomaterials having a shape consistent with the shape of the vessel.

[0049] The aluminum-silicon alloy obtained in this embodiment has an average yield strength of about 481.7 MPa, an average tensile strength of about 543.0 MPa, an average elongation of about 4.0%, and an average thermal conductivity of 110.6 w / mk.

[0050] Example 4

[0051] (1) Preparation of additive slurry: Disperse carbon nanotube powder in a solvent to prepare a carbon nanomaterial suspension, ultrasonically disperse the suspension for 30 minutes, and then add appropriate amounts of thickener and adhesive. After uniform stirring, an additive slurry is obtained. The carbon nanotube content of the obtained slurry is 50wt.%, the content of thickener and adhesive is 1wt.%, and the rest is solvent;

[0052] (2) Take a certain amount of the slurry prepared in step (1) and evenly apply it on the inner surface of a silica quartz container (volume: 200 ml) with an inner surface area of ​​100 cm 2 The slurry thickness is 1 mm, and then it is placed in a vacuum drying oven, dried at 80°C for 30 min, and then placed in the air to cool for use. The carbon content is 5 g;

[0053] (3) Under the condition of passing inert gas (such as argon, etc.), pour 700°C molten aluminum liquid into the silica quartz container with the inner surface coated with carbon nanomaterial slurry in step (2) (about 500g), then stand at the molten temperature of 700°C for 3 hours, then take it out and place it in the air to cool to room temperature. Then break the silica quartz container and take out the cast aluminum silicon alloy;

[0054] (4) removing the silicon dioxide residue on the surface of the material in step (3) by grinding, thereby obtaining an aluminum silicon alloy reinforced with carbon nanomaterials having a shape consistent with the shape of the vessel.

[0055] The aluminum-silicon alloy obtained in this embodiment has an average yield strength of about 555.4 MPa, an average tensile strength of about 659.0 MPa, an average elongation of about 1.53%, and an average thermal conductivity of 68.83 w / mk.

[0056] Example 5

[0057] (1) Preparation of additive slurry: Disperse carbon nanotube powder in a solvent to prepare a carbon nanomaterial suspension, ultrasonically disperse the suspension for 30 minutes, and then add appropriate amounts of thickener and adhesive. After uniform stirring, an additive slurry is obtained. The carbon nanotube content of the obtained slurry is 60wt.%, the content of thickener and adhesive is 1wt.%, and the rest is solvent;

[0058] (2) Take a certain amount of the slurry prepared in step (1) and evenly apply it on the inner surface of a silica quartz container (volume: 200 ml) with an inner surface area of ​​100 cm 2 The slurry thickness is 1 mm, and then it is placed in a vacuum drying oven, dried at 80°C for 30 min, and then placed in the air to cool for use. The carbon content is 6 g;

[0059] (3) Under the condition of passing inert gas (such as argon, etc.), pour 700°C molten aluminum liquid into the silica quartz container with the inner surface coated with carbon nanomaterial slurry in step (2) (about 500g), then stand at the molten temperature of 700°C for 3 hours, then take it out and place it in the air to cool to room temperature. Then break the silica quartz container and take out the cast aluminum silicon alloy;

[0060] (4) removing the silicon dioxide residue on the surface of the material in step (3) by grinding, thereby obtaining an aluminum silicon alloy reinforced with carbon nanomaterials having a shape consistent with the shape of the vessel.

[0061] The aluminum-silicon alloy obtained in this embodiment has an average yield strength of about 559.4 MPa, an average tensile strength of about 665.7 MPa, an average elongation of about 1.73%, and an average thermal conductivity of 48.34 w / mk.

[0062] Example 6

[0063] The difference between this embodiment and embodiment 3 is that the standing and heat preservation time is 1 hour.

[0064] The aluminum-silicon alloy obtained in this embodiment has an average yield strength of about 456.67 MPa, an average tensile strength of about 507.0 MPa, an average elongation of about 6.34%, and an average thermal conductivity of 149.17 w / mk.

[0065] Example 7

[0066] The difference between this embodiment and embodiment 3 is that the standing and heat preservation time is 4 hours.

[0067] The aluminum-silicon alloy obtained in this embodiment has an average yield strength of about 477.67 MPa, an average tensile strength of about 543.33 MPa, an average elongation of about 3.9%, and an average thermal conductivity of 109.77 w / mk.

[0068] Example 8

[0069] The difference between this embodiment and embodiment 4 is that the standing and heat preservation time is 4 hours.

[0070] The aluminum-silicon alloy obtained in this embodiment has an average yield strength of about 558.67 MPa, an average tensile strength of about 659 MPa, an average elongation of about 1.73%, and an average thermal conductivity of 109.77 w / mk.

[0071] Comparative Example

[0072] This comparative example is a commonly used silicon carbide reinforced aluminum-based alloy, and its preparation method is as follows:

[0073] (1) The raw materials include 6061 aluminum alloy coarse powder with D50=60 μm, 6061 aluminum alloy fine powder with D50=20 μm, and silicon carbide powder with D50=20 μm, with a mass ratio of 7.5:1.5:1;

[0074] (2) mixing aluminum alloy fine powder and silicon carbide powder for 4 h at a stirring rate of 30 r / min, then adding aluminum alloy coarse powder to the obtained system, and continuing to mix at a stirring rate of 30 r / min for 4 h to obtain a mixed material;

[0075] (3) placing the mixed material into a silica gel bag and sealing it, and then isostatically pressing it at 150 MPa for 120 seconds to obtain a green compact;

[0076] (4) vacuum sintering the pressed green body: heating the green body from room temperature to 150°C at a heating rate of 2°C / min, and keeping the temperature for 50 min; then heating the green body to 400°C at a heating rate of 2°C / min, and keeping the temperature for 50 min; finally heating the green body to 620°C at a heating rate of 2°C / min, and keeping the temperature for 240 min, to obtain an ingot;

[0077] (5) The ingot was extruded at 500°C with an extrusion ratio of 30, then online quenched, and finally kept at 165°C for 12 h to obtain a silicon carbide reinforced aluminum-based alloy.

[0078] The aluminum-silicon alloy obtained in this comparative example has an average yield strength of 381.0 MPa, an average tensile strength of 402.0 MPa, an average elongation of 12.5%, and an average thermal conductivity of 228.5 w / mk.

[0079] The present invention generates silicon carbide particles through in-situ reaction, thereby effectively strengthening the aluminum-silicon alloy. Figure 1 It can be seen that with the increase of the concentration of carbon nano slurry, the silicon carbide content gradually increases; however, when the carbon content in the carbon nano slurry exceeds 50wt.%, the silicon carbide content does not increase significantly, which shows that the carbon content of 50wt.% in the carbon nano slurry has reached a peak value.

[0080] The present invention can prepare aluminum silicon alloys with different properties by changing the concentration of carbon nano slurry. As the concentration of carbon nano slurry increases, the yield strength and tensile strength of the aluminum silicon alloy gradually increase, and the elongation and thermal conductivity gradually decrease. The performance of the aluminum silicon alloy prepared by 60wt.% carbon nano slurry is close to that of the material prepared by 50wt.% carbon nano slurry. As the insulation time increases, the performance of the material gradually improves, and the carbon is almost completely reacted in about 3 hours. Further increasing the reaction time (4h) does not improve the performance of the material.

[0081] Compared with the comparative example, the yield strength, tensile strength, elongation and thermal conductivity of the in-situ generated silicon carbide reinforced aluminum silicon alloy prepared in Examples 1-8 are better than those of Comparative Example 1.

Claims

1. A method for preparing an aluminum-silicon alloy reinforced with in-situ silicon carbide generation, characterized in that: The following steps are involved: (1) Preparing an additive slurry: uniformly dispersing a carbon nanomaterial in a solvent, adding a thickener and a binder, and uniformly stirring to obtain an additive slurry; the carbon nanomaterial is any one of carbon nanotubes, graphene, and graphene oxide; the thickener is polyvinylidene fluoride, and the binder is an acrylic resin curable hot melt adhesive; the solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide, dioxane, ethanol, ethylene glycol, butanone, and toluene; the mass fraction of the carbon nanomaterial in the additive slurry is 10-60wt.%, and the sum of the mass of the thickener and the binder is 1-2wt.% of the mass of the additive slurry; (2) uniformly coating the added slurry of step (1) on the inner surface of the silicon dioxide substrate, drying and cooling, to obtain a silicon dioxide substrate with the inner surface coated with carbon nanomaterials; the coating thickness of the added slurry is 0.5-1.5 mm; (3) Under the protection of inert gas, pour the molten aluminum solution into the silicon dioxide substrate with the carbon nanomaterial coated on the inner surface in step (2), keep it at 700-800° C. for 3 hours, and cool it; The silicon dioxide substrate is removed, and the surface residue is cleaned to obtain an aluminum silicon alloy reinforced with in-situ generated silicon carbide.

2. The method for preparing an aluminum-silicon alloy reinforced with in-situ generated silicon carbide according to claim 1, characterized in that: The carbon content of the carbon nanomaterial is greater than 98%, and the grayscale is less than 1%; the silica content of the silica substrate is ≥99.9%; and the aluminum content in the molten aluminum solution is ≥99.9%.

3. The method for preparing an aluminum-silicon alloy reinforced with in-situ generated silicon carbide according to claim 1, characterized in that: The mass fraction of the carbon nanomaterial in the added slurry in step (1) is 20-50wt.%.

4. The method for preparing an aluminum-silicon alloy reinforced with in-situ generated silicon carbide according to claim 1, characterized in that: In step (2), the drying temperature is 70-90°C and the drying time is 20-50 minutes.

5. The method for preparing an aluminum-silicon alloy reinforced with in-situ generated silicon carbide according to claim 1, characterized in that: The inert gas in step (3) is argon.

Citation Information

Patent Citations

  • Manufacturing method of silicon carbide particle reinforced aluminum matrix composite material generated through in-situ hot press

    CN106893880A

  • Method for in-situ growing carbon nano-tube reinforced aluminum-based composite material on silicon micropowder surface

    CN109182813A

  • Method for preparing silicon carbide particle reinforced aluminum matrix composite material

    CN103160702A

  • Graphene, aluminum and silicon carbide composite material and preparation method and application thereof

    CN106676335A